The Greening of Canada Federal Institutions and Decisions - Doern, G. Bruce (Heritage, 2017)
Environmental matters have become increasingly important in Canadian and world policy agendas. In this study, G. Bruce Doern and Thomas Conway trace the development of Canadian environment policy, giving an in-depth account of twenty years of environmental politics, politicians, institutions, and decisions as seen through the evolution of Ottawa's policy agency, Environment Canada. The Greening of Canada is an extensively researched look at the entire period from the early 1970s to the present and is the most complete and integrated analysis yet of federal environmental institutions and key decisions. From Great Lakes pollution to the Green Plan, from the Stockholm Conference to the post–Rio Earth Summit era, the authors deal with both domestic and international events and influences on Ottawa's often abortive efforts to entrench a green agenda into national politics. The book explores the crucial relationships of institutional and political power, directing attention at the DOE and its parade of ministers, intra-cabinet battles, federal-provincial relations, business relations and public opinion, and international and Canada–U.S. relations. It also examines important topics from acid-rain policy to the politics of establishing national parks, and from the Green Plan to the realities of environmental enforcement. Employing a framework cast as the 'double dynamic' of environmental policy making, the authors show the growing struggle between the management of power among key institutions and the need to accommodate a biophysical realm characterized by increased uncertainty as well as scientific and technological controversy